Commercial bifacial silicon solar cells - Characteristics, module topology and passivation techniques for high electrical output: An overview - KL Vincent Joseph; NT Mary Rosana; J. Aravind Kumar; Antony V Samrot (Results in Engineering)
This review article examines the development of bifacial solar cells and their present commercial architectures. This involves analyzing the historical development and evaluating commercial bifacial silicon solar cell technologies upon comparing the manufacturing cost of bifacial silicon solar cells with monofacial cells. The manufacturing cost remains unchanged, and efficiencies close to the theoretical Shockley-Queisser limits are achieved. The increase in the bifacial silicon solar cells is due to the reduction in silicon wafer thickness and the increase in the transparency of the panels. Under better albedo and proper mounting angles, a typical bifacial solar panel is expected to show 50% more power conversion efficiency than the monofacial counterpart. Bifacial silicon solar cells are monofacial cells with a back surface opened with a dielectric passivated layer, and a polymer back cover is replaced with a transparent sheet. This results in no further manufacturing costs for the bifacial panels. The commercial bifacial silicon module technology is based on Passivated Emitter and Rear Contact+ (PERC+), p-type Passivated Emitter Rear Locally Diffused (p-PERL), n-type Passivated Emitter Rear Contact (n-PERC), n-type Passivated Emitter and Rear diffused (n-PERT), n-type Passivated Emitter and Rear Locally diffused (n-PERL), heterojunction (HJC), Interdigitated-Back-Contact (IBC) and Tunnel Oxide Passivated Contact (TOPCon) cells with efficiencies are close to theoretical limits by single thin film cell. The benefits gained through higher power efficiencies result in the exact levelized cost of electricity, which is the same as that of the monofacial panels, and the gain is transferred to the consumers. Moreover, common factors are reducing the thickness of the silicon wafers and bringing more transparency to the panels. Further research and optimization can improve the bifacial cell performance and efficiencies. The bifacial solar cells will play a key role in transforming net-zero carbon goals with greater efficiencies without adding extra cost to the solar panels.